An intelligent selection method based on game theory in heterogeneous wireless networks - Salih Y.K.; See O.H.; Ibrahim R.W. (Wiley Blackwell, 2023)
Bandwidth; Game theory; Heterogeneous networks; Quality of service; Radio systems; Wireless networks; Always best connected; Available bandwidth; Heterogeneous wireless network; Intelligent method; Noncooperative game; Rich media services; Vertical handovers; Wireless environment; Next generation networks